First report of a carbapenem-resistant Aeromonas veronii environmental isolate in the United States co-harboring two carbapenemase genes - Rafael Estrada; Cristian Ruiz (Journal of Global Antimicrobial Resistance)
Objectives: The spread of carbapenem-resistant bacteria (CRB), and especially carbapenemase-producing CRB, is a global public health threat. Among them, Aeromonas species are of increasing concern because these emerging opportunistic pathogens are widespread in the environment and have increasingly been found to be resistant to carbapenems. The aim of this study was to investigate the genome and carbapenem-resistance determinants of Aeromonas veronii SS-M2–3, a highly carbapenem-resistant, carbapenemase-producing, river isolate from California (U.S.). Methods: We first used disk diffusion assays to characterize the susceptibility profile to carbapenems and other antibiotics of A. veronii SS-M2–3. We next used whole-genome sequencing using the Illumina platform and bioinformatics analysis to characterize the resistome of this isolate and identify its carbapenemase genes. Results: A. veronii SS-M2–3 was resistant to all carbapenems tested and amoxicillin-clavulanic acid, whereas it was sensitive to cefotaxime and all non-β-lactam antibiotics tested. Whole genome sequencing of this isolate revealed a complex resistome that included multidrug efflux pump genes and three chromosomal β-lactamase genes. These three genes encoded for highly conserved variants (82% to 97% amino acid identity) of the ChpA3 subclass B2 metallo-carbapenemase, OXA-12 class D carbapenemase and the FOX-2 class C β-lactamase. This is the first report of an environmental A. veronni isolate from the U.S. co-harbouring two carbapenemase genes. Conclusions: These findings reveal that natural aquatic environments in the U.S. represent an underappreciated reservoir of carbapenem-resistant Aeromonas veronii isolates that can carry multiple carbapenemase genes.